Comparing ultraviolet with chlorine dioxide wipe system for vaginal ultrasound probe cleaning: critical analysis of the term 'cleaning'. (1st July 2022) - Swinney, P.; Dixon, E.; Williams, F.; Hardy, S.
Abstract : Linked article: This Correspondence comments on Kyriacou et al. Click here to view the article.